Radioanatomic image of alveolar bone crest, cementoenamel junction and dental apex in orthopantomograph 100 panoramic radiography - Rahmawati, Yeni; Azhari, A.; Sam, Belly (Universitas Padjadjaran, 2007)
Panoramic radiography can be used in most dentomaxillofacial procedures, that can give a wide coverage of teeth and supporting tissue for assisting diagnosis. The aim of this research was to obtain data about the validity of panoramic radiography for measuring radioanatomy alveolar bone crest, cementoenamel junction (CEJ), and dental apex which is useful in measuring the level of alveolar bone resorption. This descriptive research and measurement was done to 25 sample which fulfilled sample criteria from panoramic radiography result by orthopantomograph 100. This research was done with Ramfjord criteria radioanatomy point. The result of this research showed that the average value measured of alveolar bone crest from the entire region was about 41.67%, most value at the mandibular molar was about 92%, the least value at the maxillary premolar was about 0%. The average value measured of CEJ from entire region was about 11%, most value at the maxillary molar and mandibular molar about 26%, at least value at the maxillary incisor, mandibular incisor, and maxillary premolar were about 0%. The average value measured of dental apex from the entire region was about 56.33%, most value at the mandibular molar was about 96%, the least value at the maxillary premolar was about 8%. The conclusion of this research was a part of radioanatomy alveolar bone crest and a part of dental apex could be measured, while CEJ at least measured. Measurement from the three of radioanatomy point showed the mandibular molar region which was at most measured.